INTERPERSONAL COMMUNICATION AND EMOTIONAL CLOSENESS AS A RESOURCE FOR OVERCOMING FAMILY CONFLICT (Psychology Travelogs, 2025)
The article examines the problem of interpersonal communication and emotional closeness as the main factors for effectively overcoming family conflicts. Modern socio-economic and cultural transformations of society lead to increased tension in family relationships, which makes it necessary to search for new resources for harmonizing relationships. Particular attention is paid to the analysis of communication styles, the role of empathy and the features of communicative interaction in marital and child-parent relationships. The purpose of the study was to identify the features of the influence of interpersonal communication and emotional closeness on the course and overcoming of family conflicts, as well as to identify effective psychological resources that contribute to the constructive resolution of contradictions in the family environment. In the process of work, a theoretical analysis of modern approaches to the study of family communication was carried out, the concepts of emotional closeness and empathy as factors of stability of family relationships were considered. At the empirical level, a survey and psychological testing of married couples who were at different stages of family life were conducted. The main results showed that a high level of emotional closeness and developed empathetic listening skills contribute to a decrease in the frequency of conflict situations, as well as a greater willingness of partners to compromise. At the same time, the dominance of an authoritarian style of communication and insufficient ability to emotional empathy increase the likelihood of escalation of family contradictions. It was determined that an important resource in overcoming conflicts is the ability of partners to maintain open communication, which is based on mutual respect, trust and readiness for dialogue. The conclusions emphasize that interpersonal communication and emotional closeness are powerful psychological mechanisms for preventing and overcoming family conflicts. They ensure the harmonization of relationships, increase the level of family cohesion and create the basis for the formation of a healthy microclimate in the family.
Keywords: empathy; emotional closeness; communicative interaction; interpersonal communication; marital relations; family conflicts; communication styles